Biological Degradation of Natural Rubber Glove by Gram-negative Bacteria Klebsiella aerogenes - Chittella, Harika; Yoon, Li Wan *; Ramarad, Suganti; Lai, Zee-Wei (Springer, 2024)
The increasing urgency and scope of global threat posed by rubber waste have led to efforts to find sustainable and efficient solutions. The biological degradation of rubber waste has gained interest in recent years as an alternative to conventional waste management practices and widely used chemical methods. This study uses the gram-negative bacterium Klebsiella aerogenes for natural rubber glove (NRG) degradation. The study investigates the effect of temperature and pH on the growth of the bacteria and enzyme production. The biodegraded rubber was characterized by dry weight analysis, growth curve, cell viability, Schiff’s staining, and FTIR analysis. The conversion of rubber waste to enzymes was also investigated in this work. Dry weight analysis showed a maximum weight loss of 17% at pH 7 under 35 °C after 21 days. The growth curve analysis reported a maximum cell biomass of 4.12 g/L during the second week of the biodegradation process. Schiff’s staining analysis showed deep pink colouration, indicating aldehydes and ketone formation. Further confirmation of the presence of new aldehydes and ketones peaks was shown in FTIR analysis. Results also showed that the highest protein concentration of 657.02 µg/mL and enzyme laccase and manganese peroxidase (MnP) activities of 0.43 ± 0.05 IU and 0.26 ± 0.05 IU, respectively, were observed at week 2 of the biodegradation. While Klebsiella aerogenes degrades rubber waste effectively within a shorter duration than other similar studies, laccase and MnP enzymes were also significantly produced during biodegradation. Other aspects of this resource recovery pathway, such as its mechanism and technoeconomic analysis for rubber waste treatment, are worth of further exploring.